Gift Exchange versus Monetary Exchange: Theory and Evidence - Duffy, John; Puzzello, Daniela (American Economic Review, 2014)
We study the Lagos and Wright (2005) model of monetary exchange in the laboratory. With a finite population of sufficiently patient agents, this model has a unique monetary equilibrium and a continuum of non-monetary gift exchange equilibria, some of which Pareto dominate the monetary equilibrium. We find that subjects avoid the gift exchange equilibria in favor of the monetary equilibrium. We also study versions of the model without money where all equilibria involve non-monetary gift exchange. We find that welfare is higher in the model with money than without money, suggesting that money plays a role as an efficiency enhancing coordination device. ( JEL C92, D12, E40, Z13)